Design of a suitable inspection sampling plan for mitigating the quality related problems at IC production line - Nornilawati binti Hj. Yusop (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
Unpredictable work-in-process (WIP) inventory in the inspection area of an integrated circuit (IC) assembly line acts as a source of uncertain requirement of additional human resource and production lead time. When a lot of about 5000 IC units fails to pass through on the basis of the sample due to detection of more defective items than the specified acceptance number by the sampling plan and requires a 100% rectification of the lot, mobilization of additional human resources becomes necessary to expedite the inspection process. This sudden requirement of additional inspectors creates an uneasy situation for the concerned manager. With fierce competition in place, companies cannot afford to keep human resources in reserve for such purposes. As a result the manager is forced to stop or reduce the activities of other work-station(s) and spare the operator(s) to tackle the emergent situation at the inspection area. As a result the normal schedule is disrupted and the whole system of IC manufacturing line becomes unstable and undergoes some sort of nervousness. Under this kind of situation, securing outgoing quality of IC unit without lingering the production lead time and allocation of additional human resources often appear as major bottlenecks for such companies. Upon a critical study of the current practices of the assembly line to resolve the issues, several alternative sampling plans (double and multiple) have been tried which could adequately meet the current average outgoing quality limit (AOQL), a parameter indicating the level of outgoing lot quality reaching the customer. The selected sampling plan has been found to minimize the WIP level as well as system nervousness of the assembly line. With the proper adoption of this plan it would be possible to reduce the WIP by 40% and shortening the inspection time for rectification of the post sampled lot by about half of its current level. Though, the proposed sampling plan is expected to increase the average sampling number (ASN) and average total inspection (A TI), the benefits to be accrued should outweigh the drawbacks due to increased ASN and A TI as the inspection at the assembly line involves only visual observation without conducting any destructive or expensive tests. This concept can be implemented in better management of human resources in assembly line of any high volume manufacturing process requiring control of quality through sampling with visual mechanical inspection (VMI).